PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PADA KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN - Maharani, Maria; Wilandari, Angestika; Warsono (Universitas Ciputra Surabaya, 2024)
This abstract explores the impact of compensation and work discipline on employee job satisfaction at the Ministry of Environment and Forestry. Compensation, encompassing financial and non-financial rewards, recognizes employee contributions, enhancing job satisfaction and motivation for improved performance. Work discipline, reflecting responsibility and adherence to rules, significantly influences employee productivity and managerial interactions. Using quantitative research methods, the study investigates the individual effects of compensation (X1) and work discipline (X2) on job satisfaction (Y). Results indicate both variables positively and significantly affect job satisfaction (Y), with respective t-values of 5.022 and 5.328 and significances <0.05. Additionally, the combined effect (F-value 54.123) underscores their joint impact. Future research should further explore these dynamics to provide deeper insights and contribute to organizational enhancements, particularly within the Ministry of Environment and Forestry. Expanding and applying existing theories within local contexts can address identified gaps, fostering a more comprehensive understanding of employee satisfaction drivers.